2010
DOI: 10.1245/s10434-010-0938-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Intrahepatic Cholangiocarcinoma After Resection

Abstract: Preoperative CA19-9 level was a valuable clinical factor for predicting histopathologic invasiveness as well as clinical outcome. An adequate resection margin was the only modifiable factor by a surgeon during hepatic resection for ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
5
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 28 publications
5
111
5
7
Order By: Relevance
“…In the present study, although the 1-year survival rates were about the same for those with positive and negative resection margins (57.1% vs. 56.7%, respectively), the 3-and 5-year rates were much lower in those with a positive resection margin (8.0% vs. 40.0%, and 0.0% vs. 25%, respectively). Whereas the studies by Cho et al (2010) and Ribero et al (2010) included only 6.4% and 12% (respectively) with a positive resection margin, the majority of patients (58.9%) in the present study had a positive resection margin.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In the present study, although the 1-year survival rates were about the same for those with positive and negative resection margins (57.1% vs. 56.7%, respectively), the 3-and 5-year rates were much lower in those with a positive resection margin (8.0% vs. 40.0%, and 0.0% vs. 25%, respectively). Whereas the studies by Cho et al (2010) and Ribero et al (2010) included only 6.4% and 12% (respectively) with a positive resection margin, the majority of patients (58.9%) in the present study had a positive resection margin.…”
Section: Discussioncontrasting
confidence: 65%
“…The results of the present study are in line with the 1-and 3-year rates in these reviews, but the 5-year rates in the previous studies were generally higher. In recent studies (Cho et al, 2010;Ribero et al, 2012) the 1-and 3-year rates were also higher.…”
Section: Discussionmentioning
confidence: 82%
“…Repeat hepatectomy is limited by poor remnant liver function or multifocal recurrence. In addition to that, technical and anatomical difficulties make repeat hepatectomy less feasible and more difficult to perform than initial hepatectomy [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of survival in CCA patients have focused on specific subgroups-such as those at advanced stage (Park et al, 2009), receiving surgical resection (Murakami et al, 2011;Pattanathien et al, 2013;Sriputtha et al, 2013) or adjuvant therapy (Knüppel et al, 2012), or specific tumour locations (Cheng et al, 2007;Hasegawa et al, 2007;Nakagohri et al, 2008;Guglielmi et al, 2009;Bunsiripaiboon et al, 2010;Cho et al, 2010;Nuzzo et al, 2010;Li et al, 2011). In addition, most studies were retrospective, only one prospective study (Mihalache et al, 2010) has been reported, and there are none from Asian countries.…”
Section: Introductionmentioning
confidence: 99%